Turkish Girls: The Veil and a Sense of Belonging to Germany - Pinar Burcu Güner (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
This article focuses on Turkish girls who wear the veil and their sense of belonging in Germany. Data was collected in five different cities in the federal state of North Rhein Westphalia from girls who were from 13 to 21 years old. Focus group interviews, socio-economic questionnaire and life history interviews were the source for the data. The data was analysed with Grounded Theory (Charmaz 2019). The analysis interprets how being Muslim, wearing the veil, and gender intersect in defining belonging to a nation.